Impact of lecturer's personal and impersonal facebook account access on students' perceived lecturers self-disclosure, students' emotional engagement, student-lecturer communication satisfaction, and academic performance - K.R Pillai, Padma Priya (2020)
Facebook served as an excellent platform for students and lecturers to connect, with the rise of its use by academicians, given its positive features. Studies indicated the benefit of using Facebook in education. One significant issue regarding Facebook use in education is the role of lecturers’ self-disclosure in student learning. This self-disclosure can either be in the personal or impersonal mode of the lecturers’ Facebook account. While substantial studies examined how lecturers utilised Facebook in education, the impact of lecturer’s personal and impersonal Facebook account access on Students’ Perceived Intensity of Lecturers’ Self-Disclosure (SPILSD), Students’ Emotional Engagement (SEE), Student-lecturer Communication Satisfaction (SCS) and Students’ Academic Performances (SAP) were yet to be explored. Therefore, this study examined the level of SPILSD, SEE, SCS, and SAP factors on the personal and impersonal lecturers’ Facebook account. The study defined the pre-test and post-test difference before testing the hypotheses difference relating to these factors. This study used a Quasi-experimental research design, with a total of 120 students participated in the study. Participants were assigned into two groups with one group (60 students) connected to their lecturers’ personal Facebook account access. The other group (60 students) were connected to their lecturers’ impersonal Facebook account access. Participants filled out a self-administered questionnaire on week one (pre-test) and week fourteen (post-test) of the semester. The questionnaire contained questions on the SPILSD, SEE, SAP and SCS in terms of feedback and everyday conversation. This method was essential to acquire new knowledge on the Facebook platform and useful to establish an Emotion Response Theory (ERT). The results revealed that the level of SPILSD was more significant in the lecturers’ personal Facebook account compared to the impersonal account. Group analysis for the lecturers’ personal Facebook account showed a substantial difference in the level of SPILSD, SEE, SCS, and SAP. However, the lecturers’ impersonal Facebook account showed positive changes only in SPILSD, SEE, and SCS but not in SAP. Group analysis revealed that there is no impact on SPILSD, SEE, and SAP between lecturers’ personal and impersonal Facebook account, while positive changes were only found in SCS. This study contributed to the growing body of knowledge on Facebook utilisation in education by clarifying the association of lecturers’ personal and impersonal Facebook account with SPILSD, SAP, SCS, and SEE.